Foods and nutrition encyclopedia - Ensminger, Audrey H.; Ensminger,M.E; Konlande, James E; Robson, John R.K (Pegus, 1983)
"Covers the whole gamut of the three-pronged subject, foods-nutrition-health." Approximately 2800 entries intended for lay persons and professionals. Authorities who compiled the book selected topics according to interest to readers as consumers. Opposing points of view are presented in entries. While a few entries are several pages long, most are brief and concise. Tables, illustrations, cross references. Index